Infrastructure and cluster development: A case study of handloom weavers in Ethiopia - Ayele, Gezahegn; Moorman, Lisa; Wamisho, Kassu; Zhang, Xiaobo (International Food Policy Research Institute, 2010)
Rural nonfarm development plays a key role in generating employment in many developing countries. Clustering is an important form of industrial organization in the rural nonfarm sector. Based on a primary survey of both urban and rural handloom weaver clusters in Ethiopia, one of the country's most important rural nonfarm sectors, this paper examines the mechanism and performance of clustering. That cluster-based handloom production survives even in remote rural areas illustrates its vitality in restricted environments. In the absence of financial institutions, clustered producers set up interconnected trade credit linkages to ease working capital constraints. Moreover, geographical clustering enables entrepreneurs with limited capital to enter the business through shared workspaces and fine division of labor. Despite the viability of the clustering model of production operating in harsh environments, an improvement in infrastructure can further enhance firm performance in a cluster. Our survey indicates that producers in electrified towns work longer hours than those in towns without electricity. In addition, the rental cost of shared lit workspaces is minimal, attracting more poor entrepreneurs to participate in handloom production than would otherwise be possible.